LOUIS-PIERRE SIRET (1745-1797) ET LA GRAMMATICOGRAPHIE DU PORTUGAIS LANGUE ÉTRANGERE - Fonseca, Maria do Céu (2021)
Louis-Pierre Siret is a well known name in the history of foreign language teaching in France. Being from the Age of Enlightenment, the intellectual activity of this philologist reflects the grammatical thought of the time, as well as the reformist ideas of major writers from French Enlightenment, such as Du Marsais, Pluche, Radonvilliers, who he cites in his work Éléments de la langue angloise, ou méthode pratique pour apprendre facilement cette langue (Paris, 1773). Evidence of the wide spread recognition of this manual is its use in English classes at the Séminaire de Québec and the Collège-Séminaire de Nicolet, during the nineteenth century. In addition to this English grammar, Siret’s bibliography in the field of foreign language grammaticography also includes two lesser known grammars: Élémens de la langue italienne, ou Méthode pratique pour apprendre facilement cette langue (Paris, 1797) and Grammaire française et portugaise (Paris, 1799), the latter reprinted, with several changes, in 1854 by José da Fonseca (c.1788-1866). Based on the study of this PFL grammar (1st and 2nd editions), the work proposed here aims, on the one hand to evaluate the contribution of Louis-Pierre Siret in the field PFL grammaticography and, on the other, to evaluate the effects of the Enlightenment on linguistics in this field within the context of the ideological renewal already present in the Grammaire générale de Port-Royal (1660).